Wave energy resource assessment along the Southeast coast of Australia on the basis of a 31-year hindcast. (15th December 2016) - Morim, Joao; Cartwright, Nick; Etemad-Shahidi, Amir; Strauss, Darrell; Hemer, Mark
Highlights: High-resolution wave hindcast is performed and extensively validated over 31-years The highest resolution wave energy resource atlas of Southeast Australia is developed The spatial distributions of wave power are analyzed on a seasonal and annual basis. Wave power roses and combined scatter and energy diagrams are presented at locations. Annual electrical power outputs are determined for different wave energy converters. Abstract: In this study, a long-term assessment of the wave energy resource potential for the Australian southeast shelf is performed from deep to shallow water, based on a 31-year wave hindcast. The hindcast, covering the period from 1979 to 2010, has been performed at high spatio-temporal resolution with the wave energy transformation model SWAN using calibrated source-term parameters. The model has been applied with a variable spatial resolution of up to approximately 500 m and at 1 h temporal resolution and driven with high-resolution, non-stationary CFSR wind fields and full 2D spectral boundary conditions from WaveWatch III model. Model validation was conducted against wave measurements from multiple buoy sites covering 10–31 years and showed a relatively high correlation between hindcast and measured significant wave height ( H s ) and mean wave direction ( θ m ). Maps of wave power resource distribution for annual and seasonal mean potential were generated along with the maps of resource reliability and variability. The high resolution allowed us to perform in-depth analysis of wave power characteristics, providing resource knowledge on seasonal and longer-term variability necessary for reliable and optimal design of wave technology. The most promising area for wave power exploitation was found to be the central coast of New South Wales, where various high-energy hotspots were selected for a further analysis. For each of the considered hotspots, the wave power magnitude, variability and consistency were carefully assessed and characterized by means of sea state parameters and mean wave directions. Finally, estimates of electric power outputs from different types of pre-commercial wave energy converter devices were drawn for each hotspot based on the wave data hindcast and discussed.